Preparatory EEG spectral power and coherence in biathlon rifle shooting: a pilot study - Hoedlmoser, K.; Sattlecker, G.; Finkenzeller, T.; Gallicchio, G. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Expert shooting performance is preceded by an increase in frontal midline theta (FmTheta), suggesting an increase in the top-down working memory activation1, and by lower left temporal-frontal upper alpha coherence^2, suggesting lower engagement in conscious processing of explicit knowledge to control motor execution. The aim of the present pilot study was to assess the feasibility of processing EEG data recorded in conditions of high physical load, such as in biathlon. We expected shooting performance to be preceded by changes in FmTheta power and in left temporal-frontal upper alpha coherence. We further hypothesized the intense physical exercise to impair shooting performance and disrupt preparatory cortical activity.